The Nuba Mountains Cease-Fire Agreement (Tufts Archival Research Center, 2005)
This document is an agreement between the Government of Sudan and the Sudan Peoples' Liberation Movement/Nuba reaffirming their will to negotiate an internationally monitored cease-fire agreement to cover the Nuba Mountains, supervised by a Joint Military Commission (JMC) including third-party participation. It also includes a calendar for implementation, and explanations.